Molecular mechanisms of heterosis under drought stress in maize hybrids Zhengdan7137 and Zhengdan7153 - Dai, Kai; Zhang, Zhanyi; Wang, Sen; Yang, Jiwei; Wang, Lifeng; Jia, Tengjiao; Li, Jingjing; Wang, Hao; Song, Song; Lu, Yuncai; Li, Huiyong (Frontiers in Plant Science, 2024)
Maize is one of the most successful crops in utilizing heterosis which significantly improves maize stresses resistance and yield. Drought is a destructive abiotic stress that significantly reduces crop yield, particularly in maize. Drought stress and rewatering frequently occur during the growth and development of maize; however, the molecular mechanisms of heterosis under drought stress and re-watering have rarely been systematically investigated. Zhengdan7137 and Zhengdan7153 are two maize hybrid varieties with robust heterosis, and separately belongs to the SS×NSS and Reid×Tangsipingtou heterotic groups. 54 transcriptomes of these two hybrids and their parental inbred lines were analyzed under well-watering (WW), water-deficit (WD), and re-watering (RW) conditions using RNA-Seq. In this study, we identified 3,411 conserved drought response genes (CDRGs) and 3,133 conserved re-watering response genes (CRRGs) between Zhengdan7137 and Zhengdan7153. When comparing CDRGs and CRRGs to overdominance and underdominance genes, we identified 303 and 252 conservative drought response overdominance genes (DODGs) and underdominance genes (DUDGs), respectively, and 165 and 267 conservative re-watering response overdominance genes (RODGs) and underdominance genes (RUDGs), respectively. DODGs are involved in stress response-related processes, such as L-phenylalanine metabolism, carbohydrate metabolism, and heat response, whereas DUDGs are associated with glucose metabolism, pentose-phosphate shunt, and starch metabolism. RODGs and RUDGs contribute to the recovery of hybrids from drought stress by upregulating cell propagation and photosynthesis processes, and repressing stress response processes，respectively. It indicated overdominant and underdominant genes conservatively contributed to hybrid heterosis under drought stress. These results deepen our understanding of the molecular mechanisms of drought resistance, uncover conservative molecular mechanisms of heterosis under drought stress and re-watering, and provide potential targets for improving drought resistance in maize.